Optimizing international trade: Strategies for retaining or taking over transport remit in Poland’s import and export landscape—A case study of Company X - Joanna Bednarz; Monika Grottel; Anna Sperska; Giuseppe T. Cirella; Michael Suchanek; Aneta Oniszczuk-Jastrząbek; Ernest Czermanski (PLoS ONE, 2025)
This study explores the economic implications of transport remit management in Poland’s international trade landscape, with a particular focus on the operations of a medium-sized Polish forwarding company (Company X). Employing a mixed-methods approach, the research combines quantitative analysis of government datasets, firm-level transaction data, and qualitative insights from a targeted industry survey. The case study of Company X reveals notable reluctance among Polish enterprises to assume transport remit responsibilities, particularly in import operations, due to preferences for foreign partners, limited experience with international logistics, and concerns about administrative complexity. Analysis of Incoterms® usage patterns highlights a partial recovery of forwarding services in 2021, reflecting post-pandemic adjustments in logistics strategy. While the findings cannot be generalized to the entire Polish economy, they offer a detailed, data-driven illustration of the microeconomic factors influencing transport remit decisions. The study underscores the need for transparent procedures, legal clarity, and targeted training initiatives to increase the uptake of transport remit services by domestic firms. By improving internal capabilities and reducing reliance on foreign partners, Poland could strengthen its position in global trade and enhance value creation in the logistics sector.